Biology and Management of Whitehead Broom in Pastures - Brent Sellers; Lauren Butler; James McWhorter (EDIS, 2019)
Whitehead broom (Spermacoce verticillata; Figure 1), also known as shrubby false buttonweed or southern larraflower, is becoming problematic in south Florida pastures, hayfields, and rights-of-way. With the first recorded herbarium specimen dating back to 1956, this plant was likely introduced to Florida during the late 1940s or early 1950s. Since this time, it has increased in range throughout central and south Florida and has become a serious problem. To date, there are few options to control this species. This 3-page fact sheet is a minor revision written by Brent Sellers, Lauren Butler, and James McWhorter, and published by the Agronomy Department, December 2019.